Characterization of High-Power Turbomachinery Tilting Pad Journal Bearings: First Results Obtained on a Novel Test Bench - Enrico Ciulli (Lubricants, 2018)
Tilting pad journal bearings are usually employed in turbomachines for their stable behavior at high rotational speeds. Devoted test rigs have been realized to validate the predictions of theoretical models. However, the design of new high-performance and large-size bearings needs to be supported by experimental investigations on high-performance large test rigs. The main characteristics of a recently built facility for testing large tilting pad journal bearings with diameters from 150 to 300 mm are described in this work. The test rig is versatile and can be used to test bearings of different size, configurations and to investigate the influence of many parameters, even the effect of misalignment. Sample results of the static characterization of a four-pad high-performance tilting pad journal bearing are reported evidencing some transient effects. A few sample dynamic results are also reported. The presented experimental results demonstrated the capabilities of the rig for investigating the static and the dynamic characteristics of the bearings accurately measuring slow and fast variables.